Rightwing populism: an element of neodemocracy - Beyme, Klaus von (Springer International Publishing, 2019)
This book, written by a prominent German political scientist and specialist for political theory and comparative government, analyses right-wing populism as a topical theme of postmodern party systems in Europe and the United States
Keywords: Europa; USA